Human Rights and Relativism Through the Lens of Developing Nations Case Study of Indonesia’s Ratification on CEDAW - Lubis, Muhammad Rizki Akbar (Universitas Negeri Semarang, 2023)
Universalists argue that human rights as laid out by current human rights law embodies universal ideals and rights that are universally relevant and applicable to all people. However, some relativists have questioned this idea, pointing out that ethical systems should evolve in the context of local cultures and not assume its universal applicability. It arises a question whether human rights indeed a universal concept that should be assumed to all nations irrespective of its cultural differences. Especially in the context of most developing nations that have their own cultural philosophies and societal conducts, it is intriguing to assess how does the